Changing the Attitudes and Beliefs of Pre-service Primary Teachers Towards Mathematics - Dorian Stoilescu (Southeast Asian Mathematics Education Journal, 2017)
The importance of preparing primary educators capable of successfully teachingmathematics has been extensively emphasized in educational research. However, it is widely acknowledged that pre-service teachers in primary education start their career with poor attitudes and a great degree of anxiety towards mathematics. As such, primary education has been under severe criticism for not being able to provide their pre-service teachers with an adequate set of skills and attitudes towards mathematics. This paper discusses several cases and searches for possible explanations that are perpetuating this state. As well, this theoretical paper gives some recommendations for decreasing mathematics anxiety and improving mathematical knowledge for pre-service teachers in primary education.